2010
DOI: 10.1104/pp.109.151985
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Toolkit of Plant Cell Wall Glycan-Directed Monoclonal Antibodies    

Abstract: A collection of 130 new plant cell wall glycan-directed monoclonal antibodies (mAbs) was generated with the aim of facilitating in-depth analysis of cell wall glycans. An enzyme-linked immunosorbent assay-based screen against a diverse panel of 54 plant polysaccharides was used to characterize the binding patterns of these new mAbs, together with 50 other previously generated mAbs, against plant cell wall glycans. Hierarchical clustering analysis was used to group these mAbs based on the polysaccharide recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
403
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(415 citation statements)
references
References 46 publications
9
403
0
3
Order By: Relevance
“…JIM5 is specific for partially methylesterified HG (up to 40%; Vandenbosch et al, 1989;Knox et al, 1990;Willats et al, 2000), whereas CCRC-M36 is specific for the unsubstituted RG I backbone that is found in Arabidopsis seed mucilage (Young et al, 2008;Arsovski et al, 2009;Pattathil et al, 2010). CCRC-M36 strongly labeled the periphery of the mucilage halo in wild-type seeds ( Fig.…”
Section: Sos5 and Cesa5 Act Independently To Promote Seed Mucilage Admentioning
confidence: 99%
See 1 more Smart Citation
“…JIM5 is specific for partially methylesterified HG (up to 40%; Vandenbosch et al, 1989;Knox et al, 1990;Willats et al, 2000), whereas CCRC-M36 is specific for the unsubstituted RG I backbone that is found in Arabidopsis seed mucilage (Young et al, 2008;Arsovski et al, 2009;Pattathil et al, 2010). CCRC-M36 strongly labeled the periphery of the mucilage halo in wild-type seeds ( Fig.…”
Section: Sos5 and Cesa5 Act Independently To Promote Seed Mucilage Admentioning
confidence: 99%
“…Wild-type, cesa5-1, and sos5-2 seeds were labeled with JIM13 [epitope: Knox et al, 1991;Yates and Knox, 1994;Yates et al, 1996;Majewska-Sawka and Nothnagel, 2000], MAC207 [epitope: a-GlcA-(1,3)-a-GalA-(1,2)-a-Rha; Bradley et al, 1988;Pennell et al, 1989;Yates and Knox, 1994;Yates et al, 1996;Pattathil et al, 2010], JIM8 (epitope: arabinogalactan; Pennell et al, 1991;Majewska-Sawka and Nothnagel, 2000), and CCRC-M7 (epitope: recognizes 6-linked b-D-Gal oligomers that contain arabinose; Puhlmann et al, 1994;Steffan et al, 1995;Pattathil et al, 2010) antibodies (Supplemental Figs. S7 and S8).…”
Section: Sos5 and Cesa5 Act Independently To Promote Seed Mucilage Admentioning
confidence: 99%
“…Monoclonal antibodies were obtained as hybridoma cell culture supernatants from laboratory stocks (CCRC series and JIM series antibodies are available from CarboSource [http://www.carbosource/net]). Detailed information about all monoclonal antibodies included in this study can be found at WallMabDB (http://www.wallmabdb.net), an online database that provides information about the immunogens used to develop the antibodies, their isotype, the cell wall polysaccharide class they primarily recognize, and detailed epitope information where available (Pattathil et al, 2010). Whole-seed immunolabeling was conducted as described (Sullivan et al, 2011).…”
Section: Immunological Analysesmentioning
confidence: 99%
“…Immunogold labeling, using CCRC-M38 (a nonmethylesterified HG-directed monoclonal antibody; Pattathil et al, 2010), was employed to visualize the localization of HG epitopes in seed coat epidermal cells. Nonmethylesterified HG is evenly distributed in the middle lamella and cell corners of seed coat epidermal cells (Fig.…”
Section: Atgatl5mentioning
confidence: 99%
“…The antibodies used were PN16.4B4 and MAC204 with a respective dilution of 1:100, 15) and the antigen-antibody complex on the membrane was detected by using ECL Plex goat--mouse IgG-Cy5 (GE Healthcare) or Alexa fluor 488 goat--rat IgM (Invitrogen) at a respective dilution of 1:2500, the signals being detected by a Typhoon 9640 image analyzer. As shown on the left of Fig.…”
Section: Notementioning
confidence: 99%